Caracterizacion de la cepa BF8 del virus de la enfermedad infecciosa de la bolsa como cepa de confrontacion - Perera, C.L.=700 1 Noda, J.; Coroas, L.I.; Alfonso, P.; Cuello, S.
(En, Es)
Ilus., 12 ref.
Keywords: AVES DE CORRAL; ENFERMEDAD DE GUMBORO; ENFERMEDADES INFECCIOSAS; EMBRIONES ANIMALES; POLLO; VACUNACION; PATOGENICIDAD; MORTALIDAD; CUBA; CEPA; HISTOPATOLOGIA